Safety Analysis of Using Scaffolding in Multi-Storey Building Projects - Lubis, Syavira Ardiba; Pasaribu, Bangun; Hasibuan, M. Husni Malik (CV. Rayyan Dwi Bharata, 2024)
Construction work is a process that involves various disciplines, resources and has its own unique characteristics, including occupational safety and health. However, in reality, in the world of construction, falling accidents still often occur. One important element in a construction project is the use of scaffolding, which is susceptible to the risk of accidents if it is not installed and used according to standards. OSHA (Occupational Safety and Health Administration) which was passed on April 28 1971 provides regulations that serve as guidelines for workers and project supervisors to ensure the K3 system in the workplace. The aim is to analyze the safety of using scaffolding in the Public Lecture Building - C Construction project at Malikulsaleh Lhokseumawe University by comparing two assessment methods, namely based on the Checklist Table, where the results of the research show that this analysis provides more certain results and makes the evaluation process easier because it provides scores or assessments in the form of numbers. , compared to using the original OSHA regulations which still do not have definite values within the limits that conclude whether its use is safe or not in the field. Thus, the use of checklists can increase certainty in identifying potential hazards that may not be covered in detail in the original regulations. Suggesting further development of scaffolding safety analysis methods that are still based on OSHA regulations or other laws passed and enforced by the government in a country but are more structured and measurable are expected to improve K3 standards in construction projects as a whole, especially in the use of scaffolding.